Uma análise dos exames de admissão ao secundário (1930-1970): subsídios para a história da educação matemática no Brasil - Machado, Rita de Cassia Gomes (2002)
This study intends to contribute to the History of Mathematics Education in Brazil from 1920 to 1960, from the analysis of Mathematics tests of entrance examination tests in secondary school. Considering theoretical-methodological studies about the history of school disciplines as references, the research tried to show that the entrance examinations constituted an obstacle to the modernization proposal of mathematics teaching in Brazil. This proposal reflected the design of the first movement of internalization of school mathematics